2021
DOI: 10.1002/jper.21-0292
|View full text |Cite
|
Sign up to set email alerts
|

Combined association of cognitive impairment and poor oral health on mortality risk in older adults: Results from the NHANES with 15 years of follow‐up

Abstract: Background: Cognitive impairment and poor oral health are frequently seen among older adults. Both conditions have been identified as risk factors for mortality. However, the combined associations of cognitive impairment and poor oral health with mortality have not been well studied and are therefore the aim of this cohort study. Methods: We analyzed data from the National Health and Nutrition Examination Survey (1999 linked with mortality data obtained from the 2015 public-use linked mortality file. Cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…We categorized the race or ethnicity as non‐Hispanic White, non‐Hispanic Black, and others (including Mexican American, other Hispanic, and other races [e.g., multi‐racial]); 2) behavioral factors (smoking status [non‐smoker, former smoker, or current smoker], alcohol intake [≥12 drinks/year or <12 drinks/year], and dental visit [<1 year, 1–3 years, or >3 years]); and 3) health conditions (diabetes mellitus, hypertension, dyslipidemia, obesity, abdominal adiposity, cardiovascular disease, and cancer). We described the detailed definitions and categories of health conditions in Supplementary Table S1 in the online Journal of Periodontology , as the previous study 33 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We categorized the race or ethnicity as non‐Hispanic White, non‐Hispanic Black, and others (including Mexican American, other Hispanic, and other races [e.g., multi‐racial]); 2) behavioral factors (smoking status [non‐smoker, former smoker, or current smoker], alcohol intake [≥12 drinks/year or <12 drinks/year], and dental visit [<1 year, 1–3 years, or >3 years]); and 3) health conditions (diabetes mellitus, hypertension, dyslipidemia, obesity, abdominal adiposity, cardiovascular disease, and cancer). We described the detailed definitions and categories of health conditions in Supplementary Table S1 in the online Journal of Periodontology , as the previous study 33 …”
Section: Methodsmentioning
confidence: 99%
“…We described the detailed definitions and categories of health conditions in Supplementary Table S1 in the online Journal of Periodontology , as the previous study. 33 …”
Section: Methodsmentioning
confidence: 99%
“…More research is therefore necessary on the association between chewing function and general health in the edentulous population. Recent studies have linked edentulism to mortality in the older population [8,9]. It was reported that the edentulism-mortality link (16.1%) could be partly explained by the elevated cardiovascular risk [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have linked edentulism to mortality in the older population [8,9]. It was reported that the edentulism-mortality link (16.1%) could be partly explained by the elevated cardiovascular risk [8]. Thus, the mortality risk of edentulous older adults might arise from a complex interplay of oral diseases (e.g., periodontal infections and severe caries lesions) that eventually can cause general health problems, including higher cardiovascular risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Oral health, enabling natural eating, speaking, smiling, and socializing, plays a vital role in overall health ( 5 , 6 ). Deterioration of oral health can lead to various adverse health outcomes, such as cardiovascular diseases ( 7 ), cognitive impairment ( 8 ), disability ( 9 ), and all-cause mortality ( 10 ). However, studies have suggested that dental diseases could be prevented and reversed ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%